Keragaman Konsep Sulṭān dalam Al-Qur'an: Analisis Tematik Tafsir Al-Azhar oleh Hamka - Siregar, Mohd. Rizky (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to explore the interpretation of the word "Sulṭān" in the context of Tafsir Al-Azhar by Buya Hamka. This research uses a qualitative study approach with a descriptive-analytical method to analyse how Hamka, in his famous tafsir Al-Azhar, understands and explains the concept of "Sulṭān" based on Qur'anic verses. The descriptive method is used to identify and describe Hamka's interpretation of the word "Sulṭān", while the analytical method is used to explore the implications and applications of this concept in the context of Muslim life and thought. The results of this study reveal that Hamka sees the word "Sulṭān" in the Qur'ān not only as a reference to human rulers, but also as an attribute attached to Allah SWT Himself in the context of His authority and power. Hamka's interpretation associates this word with concepts such as hikmah (wisdom), 'adl (justice), and rahmah (compassion), reflecting his holistic view of Qur'anic teachings. Thus, this study not only explores the interpretation of the text in depth but also examines the relevance of the concept of "Sulṭān" in understanding Islamic teachings more broadly. The implications of this interpretation can provide a better understanding of how the teachings of the Qur'ān can be applied in the context of the social and spiritual life of Muslims, as well as contributing to contemporary tafsir thought.